Analysis of Online Sales Contracts Using Shopee Paylater in the Perspective of Fiqh Muamalah - Fauziah, Ai Samrotul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to explore the suitability of the deferred payment mechanism through Shopee PayLater with the principles of Islamic law, especially in terms of debt-receivables transactions and the prohibition of usury. This study uses a qualitative approach with descriptive analysis of secondary data to explore issues of legality and morality of BNPL transactions in the context of Islamic economics. Based on an analysis of sharia provisions, it was found that the existence of additional fees and late payment fines in the Shopee PayLater system can be categorized as the practice of usury, which is contrary to Islamic teachings. The findings of this study are expected to provide a better understanding of the impact of the delayed payment system in electronic commerce and provide recommendations related to the implementation of transactions that are more in accordance with sharia principles.